2006
DOI: 10.1038/ng1748
|View full text |Cite|
|
Sign up to set email alerts
|

Germline KRAS mutations cause Noonan syndrome

Abstract: Noonan syndrome (MIM 163950) is characterized by short stature, facial dysmorphism and cardiac defects. Heterozygous mutations in PTPN11, which encodes SHP-2, cause approximately 50% of cases of Noonan syndrome. The SHP-2 phosphatase relays signals from activated receptor complexes to downstream effectors, including Ras. We discovered de novo germline KRAS mutations that introduce V14I, T58I or D153V amino acid substitutions in five individuals with Noonan syndrome and a P34R alteration in a individual with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
587
2
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(628 citation statements)
references
References 28 publications
25
587
2
9
Order By: Relevance
“…Phenotypically overlapping Costelo syndrome and cardio-facio-cutaneous syndrome are caused by gain-of-function HRAS mutation and KRAS/BRAF/MEK1/MEK2 mutation, respectively (Aoki et al, 2005;Niihori et al, 2006;RodriguezViciana et al, 2006). Some Noonan syndrome cases are also attributed to gain-of-function mutations in SOS1 that encodes the RAS guanine nucleotide exchange factor or KRAS (Schubbert et al, 2006;Roberts et al, 2007;Tartaglia et al, 2007). The observations collectively indicate that aberrant activation of the SHP-2-RAS-ERK pathway plays a key role in these overlapping developmental disorders (Gelb and Tartaglia, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Phenotypically overlapping Costelo syndrome and cardio-facio-cutaneous syndrome are caused by gain-of-function HRAS mutation and KRAS/BRAF/MEK1/MEK2 mutation, respectively (Aoki et al, 2005;Niihori et al, 2006;RodriguezViciana et al, 2006). Some Noonan syndrome cases are also attributed to gain-of-function mutations in SOS1 that encodes the RAS guanine nucleotide exchange factor or KRAS (Schubbert et al, 2006;Roberts et al, 2007;Tartaglia et al, 2007). The observations collectively indicate that aberrant activation of the SHP-2-RAS-ERK pathway plays a key role in these overlapping developmental disorders (Gelb and Tartaglia, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…[16][17][18][19] Along these lines, defects in human development have recently been associated with Ras isoform-specific functions. [19][20][21] The different magnitude of oncogenic Ras isoform signaling further supports signal specificity of Ras isoforms. Although there is some controversy about the differential ability of Ras isoforms to activate downstream effectors, some studies suggested that H-Ras strongly activates the PI3K/Akt pathway, while K-Ras is a more potent activator of the Raf/MAPK pathway.…”
Section: Functional Differences Of Ras Isoforms and Differential Gap mentioning
confidence: 99%
“…These disorders share similar phenotypic features including: short stature, short neck, cardiovascular defects, facial anomalies, learning difficulties and predisposition to developing cancers. Genetic screening of patients with Noonan syndrome has identified gain of function mutations in PTPN11 (50%), Sos1 (20%) and K-Ras (5%) [12][13][14][15]. H-Ras is mutated in >85% of Costello syndrome cases and K-Ras (7%), B-Raf (>35%), MEK (13%) are mutated in CFC syndrome [16][17][18].…”
Section: Introductionmentioning
confidence: 99%